Insight into development of job-related well-being: the role of four job crafting strategies and psychological needs - Baka, Lukasz; Prusik, Monika; Derbis, Romuald (Frontiers in Psychology, 2025)
By applying the job demand-resources and self-determination theories, this three-wave study (with eight-month intervals) examined direct and indirect (via satisfaction and frustration of psychological needs at work) effects of four job crafting strategies on two dimensions of job-related well-being (engagement and exhaustion). It was hypothesized that approach-oriented job crafting related to increasing structural/social job resources and challenge demands leads to higher needs satisfaction, which result in higher engagement, over time. In contrast, avoidance-oriented job crafting related to decreasing hindrance demands is associated with higher needs frustration and further with higher exhaustion. Data were collected among 839 social service workers. All three waves of the study were conducted during the coronavirus pandemic. Structural equation modeling supports these hypotheses in part. The positive direct relation between the crafting of hindrance demands and exhaustion was not confirmed, in contrast to the indirect effect of psychological needs frustration. Of the three approach-oriented job crafting strategies, only increasing structural resources was direct related to work engagement. Increasing structural resources and challenge demands were positively associated with needs satisfaction. Contrary to them increasing social resources resulted in lower needs satisfaction. Higher needs satisfaction led to higher work engagement. The results were discussed in relation to competing motives for building relationships and strengthening one’s own competences.